AIDS mortality in African migrants living in Portugal: evidence of large social inequalities. Issue 6 (11th June 2009) - Williamson, L M; Rosato, M; Teyhan, A; Santana, P; Harding, S
Abstract : Objective: To examine infectious disease and AIDS mortality among African migrants in Portugal, gender and socio-economic differences in AIDS mortality risk, and differences between African migrants to Portugal and to England and Wales. Methods: Data from death registrations, 1998–2002, and the 2001 Census were used to derive standardised death rates by country of birth, occupational class (men only), and marital status. Results: Compared with people born in Portugal, African migrants had higher mortality for infectious diseases including AIDS. There was considerable heterogeneity among Africans, with those from Cape Verde having the highest mortality. Death rates were more than five times higher among those who were unmarried than those who were. A larger proportion of Africans were unmarried accounting for some excess mortality. Death rates were also higher among men from manual occupational classes than among men from non-manual. A comparison with England and Wales shows that death rates for infectious disease and AIDS in Portugal are much higher and Africans in Portugal also fare worse than Africans in England and Wales. Conclusion: AIDS mortality rates were higher among Africans than those born in Portugal and were associated with socio-environmental factors. Further research is required to interpret the excess mortality among Africans and there is a need to ensure the inclusion of relevant data items on ethnicity in national monitoring and surveillance systems.